Violencia de género e inequidad social en los/las estudiantes de la carrera de Psicopedagía y Psicología Educativa de la Universidad Nacional de Chimborazo - Zúñiga Abarca, Evelyn Tatiana (2021)
The research called "Gender violence and social inequity in students of the Educational Psychology Psychopedagogy major at the National University of Chimborazo", aimed to analyze the relationship between gender violence and social inequity in students of the sixth semester "A" Psychopedagogy major and the eighth semester "A" of Educational Psychology at the National University of Chimborazo. Since this type of problem is present in our environment. Methodologically, this research work had a mixed approach and the design a non-experimental research, the type of research was descriptive, basic for its objectives, field for the place; and the type of study was crosssectional. To collect the information, a Psychometric Test to measure Gender Violence and a Questionnaire to determine the existence of Social Inequity were used as instruments, which were applied to 20 students of the Psychopedagogy major and 26 students of the Educational Psychology major, giving a total of 46 students surveyed. The results conclude that there is a low percentage of psychological violence, generated by jealousy from partners; in the same way, discrimination between teachers-students and vice versa is evidenced in different percentages. Finally, the application of the Pearson correlation method in the variables understudy showsthat there is a relationship between them,since there issocial inequity, therefore, gender violence can be generated with greater probability.